Estágio supervisionado na Educação de Jovens e Adultos: um relato de experiência. - BRITO, Waldir Wellington Nascimento (2023)
The presented text describes a report on the experience of supervised internship in Youth and Adult Education (EJA), carried out by students of the Bachelor's degree in Pedagogy at a municipal school in Bragança, Pará, in September 2019. The supervised internship is a mandatory activity of the course and aims to provide a connection between theory and practice, allowing future professionals to observe, participate, reflect, and exchange ideas with teachers and students. The internship report was structured into four parts. The first part presents the characterization of the school, located in Bragança, with its facilities and available resources. The school offers education for youth and adults, covering different stages of EJA. The school's Political Pedagogical Project seeks to understand and respect the needs and realities of the students, using generative themes and contextualization to enhance the learning process. The second part of the report describes the subjects of EJA, who are adult workers from diverse occupations and socioeconomic conditions. Many of these students face learning difficulties due to their daily responsibilities and fatigue. The third part addresses the pedagogical characteristics observed during the classes. The supervising teacher utilizes strategies such as relating the content to the students' life experiences, presenting short written content on the board, and proposing reading and writing activities for the students to practice autonomously. The interaction between teacher and student is fundamental for the success of the teachinglearning process. In the final part, the interns describe the intervention project they developed, which was based on the activities carried out in the classroom. The project focused on the theme of "Textual Genres and Ethnomathematics" and aimed to address the students' difficulties in reading, writing, and basic mathematics, seeking alternatives to assist them in understanding the content. Activities were conducted that linked the project to the school timetable, aiming to develop intervention practices on textual genres and ethnomathematics for EJA students. In summary, the report on the supervised internship in EJA describes the experience of Pedagogy students in a municipal school, highlighting the importance of the internship as an opportunity for learning, reflection, and connection between theory and practice. The report emphasizes the characterization of the school, the subjects of EJA, the pedagogical characteristics observed in the classes, and the development and implementation of an intervention project. This experience allowed the interns to experience the school reality, understand the challenges of EJA, and contribute to the construction of pedagogical knowledge.